2002
DOI: 10.1021/bi011816v
|View full text |Cite
|
Sign up to set email alerts
|

pKa Perturbation in Genomic Hepatitis Delta Virus Ribozyme Catalysis Evidenced by Nucleotide Analogue Interference Mapping

Abstract: The Hepatitis Delta Virus (HDV) ribozyme was the first RNA enzyme proposed to use a proton-transfer mechanism for catalysis. Previous biochemical evidence suggested that the genomic HDV ribozyme promotes cis-cleavage using cytosine 75 whose pK(a) is perturbed within the active site. Here we present further biochemical evidence for the involvement of C75 in proton transfer, as well as evidence to support a plausible mechanism for C75 pK(a) perturbation. Nucleotide analogue interference mapping (NAIM) experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 47 publications
1
61
0
Order By: Relevance
“…Kinetic and mutagenesis studies on the HDV ribozyme support a cleavage mechanism involving general acid-base catalysis by C75 (Perrotta et al 1999;Nakano et al 2000;Oyelere et al 2002;Das and Piccirilli 2005;Perrotta et al 2006). Two models have been advanced for how C75 participates in general acid-base catalysis, as recently summarized by Nakano and Bevilacqua (2007).…”
Section: Introductionmentioning
confidence: 93%
“…Kinetic and mutagenesis studies on the HDV ribozyme support a cleavage mechanism involving general acid-base catalysis by C75 (Perrotta et al 1999;Nakano et al 2000;Oyelere et al 2002;Das and Piccirilli 2005;Perrotta et al 2006). Two models have been advanced for how C75 participates in general acid-base catalysis, as recently summarized by Nakano and Bevilacqua (2007).…”
Section: Introductionmentioning
confidence: 93%
“…2 and Scheme 1 pathway "G") [27,87]. Isocytosine is a structural isomer of cytosine, recognizing both guanine (iCG) and cytosine (iCC) in reversed and normal WatsonCrick interactions, respectively [88].…”
Section: Syntheses Of Nucleic Bases From Formamidementioning
confidence: 99%
“…Moreover, pH-rate profiles for the reaction in the absence of Mg 2+ and for mutants designed to disrupt binding of the proposed active site ion are inverted relative to the reaction of the native HDVr in Mg 2+ Chen et al 2013). Phosphorothioate interference studies have revealed sites of potential site-bound metal ion interactions via coordination to one or more nonbridging oxygens, including the pro-R P position of the scissile phosphate (Jeoung et al 1994;Fauzi et al 1997;Prabhu et al 1997;Raines and Gottlieb 1998;Oyelere et al 2002;Das and Piccirilli 2005;Thaplyal et al 2013). Thiophilic metal ion rescue experiments have been interpreted as supporting a catalytic metal ion interacting with this position.…”
Section: Introductionmentioning
confidence: 99%